Inlfuence Of Lecturers’ Perceptionon Creation Of Intellectual Property In Universities In South-West, Nigeria - Oboh, Ransome A.; Okwilagwe, O. A. (Advances in Social Sciences Research Journal, 2019)
This is part of a doctoral dissertation aimed at investigating the influence of lecturers’ perception on creation of Intellectual Property (IP) in universities in Southwest, Nigeria.Intellectual property is a legal and economic instrument used in disseminating research results, and for generating revenueby universities. Previous studies identified low level of IP creation by lecturers in theseuniversities. To increase IP creation, lecturers’ perception may be a critical factor to investigate. To conduct the investigation, the study adopted the descriptive survey design of the correlational type. Equal allocation sampling technique was used to select 864 (11.25%) from a population of 7,678 lecturers in the three types of universities. Eight items were used to measure creation of IPand 16items were used to measure lecturers’ perception of IP. Reliability coefficient of creation of IPwas 0.83and lecturers’ perception was 0.79.Percentage, mean, t test, correlation,multiple regression and analysis of variance were used to analyse the data at 0.05 level of significance.Findings showed that creation of IPwas high (60.35%) and significant (=2.63). Lecturers’ perception of IP was (=2.55). Lecturers’ perception were also significant and showed positive relationship (r = .56) on creation of IP. Lecturers’ perception (β = 46made significant relative contribution to creation of IP in the universities.Creation of IP in universities in South-west, Nigeriacan be increased if lecturers’ perception of IP is enhanced in the universities.